PENGARUH PENERAPAN SISTEM AKUNTANSI PEMERINTAH DAERAH, SISTEM PELAPORAN, DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH (Pada Organisasi Perangkat Daerah di Kabupaten Rokan Hulu) - Muslimah Winda; Taufik Taufeni; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of the local government accounting systemimplementation, reporting system, and compliance with laws and regulations on theperformance accountability of local government institutions. The data used in this studyis primary data using the questionnaire method. The questionnaire method is to distributea list of question (questionnaires) that will be answered and answered by therespondents, namely the parties who carry out the function of the head of the section inthe local government. The research sample was 90 people. The hypothesis is used usingmultiple linear regression analysis. The results of the study indicate that the applicationof the local government accounting system has an positive effect on the accountability ofthe performance of government institutions. The reporting system positive effects theaccountibility of the performance of local government institutions, and compliance withlaws and regulations positive effects the accountability of the performance of localgovernment institutions.Key words: implementation of local government accounting systems, reporting systems,compliance with laws and regulations, accountability for performance oflocal government institutions.